2015
DOI: 10.1039/c5nj01149c
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the reactions between the DNA bases and a model α,β-unsaturated oxoaldehyde

Abstract: Two sets of adducts of 2′-dC with a model oxoenal were characterised based on 2D NMR spectroscopy. DFT calculations indicated that two mechanisms can be involved in these compounds formation. The instability of one of these products leads to deamination of 2′-dC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…The preferred reactivity of BDA with dC rather than dG and dA, as reported by Byrns et al (2002) was also observed by Pluskota-Karwatka et al (2015). Similar oxadiazabiclyclooctaimine adducts were reported as before.…”
Section: Binding To Dnasupporting
confidence: 83%
See 3 more Smart Citations
“…The preferred reactivity of BDA with dC rather than dG and dA, as reported by Byrns et al (2002) was also observed by Pluskota-Karwatka et al (2015). Similar oxadiazabiclyclooctaimine adducts were reported as before.…”
Section: Binding To Dnasupporting
confidence: 83%
“…() was also observed by Pluskota‐Karwatka et al. (). Similar oxadiazabiclyclooctaimine adducts were reported as before.…”
Section: Assessmentsupporting
confidence: 71%
See 2 more Smart Citations